Cortical Lewy Body Dementia - W. R. G. Gibb (Behavioural Neurology)
In cortical Lewy body dementia the distribution of Lewy bodies in the nervous system follows that of Parkinson's disease, except for their greater profusion in the cerebral cortex. The cortical tangles and plaques of Alzheimer pathology are often present, the likely explanation being that Alzheimer pathology provokes dementia in many patients. Pure cortical Lewy body dementia without Alzheimer pathology is uncommon. The age of onset reflects that of Parkinson's disease, and clinical features, though not diagnostic, include aphasias, apraxias, agnosias, paranoid delusions and visual hallucinations. Parkinsonism may present before or after the dementia, and survival duration is approximately half that seen in Parkinson's disease without dementia.